2011
DOI: 10.1007/s00170-011-3703-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of backpropagation neural network for spindle vibration-based tool wear monitoring in micro-milling

Abstract: This study develops a micro-tool condition monitoring system consisting of accelerometers on the spindle, a data acquisition and signal transformation module, and a backpropagation neural network. This study also discusses the effect of the sensor installations, selected features, and the bandwidth size of the features on the classification rate. To collect the vibration signals necessary for training the system model and verifying the system, an experiment was implemented on a micro-milling research platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…For the implementation of monitoring schemes, most of the current studies on TCM are based on empirical analysis [10], or sensing-oriented approaches such as motor current analysis [11], vibration analysis [12]- [15], and acoustic emission (AE) [8], [16], [17], or some of the combination approaches [18], [19]. In [10], Rahman et al found that the premature failure was the major factor that affected the micromilling tool life.…”
mentioning
confidence: 99%
“…For the implementation of monitoring schemes, most of the current studies on TCM are based on empirical analysis [10], or sensing-oriented approaches such as motor current analysis [11], vibration analysis [12]- [15], and acoustic emission (AE) [8], [16], [17], or some of the combination approaches [18], [19]. In [10], Rahman et al found that the premature failure was the major factor that affected the micromilling tool life.…”
mentioning
confidence: 99%
“…The advantage of AE is that the signal measured is a source of engagement where the chip is formed, as were introduced in [10,11]. Vibration has also been one of the most widely studied signals for monitoring due to its convenient implementation; see for examples in [12,13]. Hsieh et al [13] detected tool wear with an accelerometer and showed that the vibration signals could be implemented in a neural network and used for micro-milling monitoring.…”
Section: The Backgroundmentioning
confidence: 98%
“…Vibration has also been one of the most widely studied signals for monitoring due to its convenient implementation; see for examples in [12,13]. Hsieh et al [13] detected tool wear with an accelerometer and showed that the vibration signals could be implemented in a neural network and used for micro-milling monitoring. Generally the vibration is brought by the cutting force variations, and as a result the vibration is less http://dx.doi.org/10.1016/j.mechatronics.2015.04.017 0957-4158/Ó 2015 Elsevier Ltd. All rights reserved.…”
Section: The Backgroundmentioning
confidence: 99%
“…As the critical aspect of the operation is the cutting-tool state (cutting-tool wear), sensors applied in tool condition monitoring are commonly used. A large number of research works have been conducted for cutting-tool monitoring and some of them applied to micromilling operations on hardened steels can be found in [12][13][14][15]. In general, the monitoring module is composed of a sensor system unit, amplification and conditioning unit, and a signal processing and feature extraction unit.…”
Section: Monitoring Modulementioning
confidence: 99%
“…In general, the monitoring module is composed of a sensor system unit, amplification and conditioning unit, and a signal processing and feature extraction unit. In tool condition monitoring systems for machining operations, different sensors have been successfully applied, such as dynamometers [12,14,16,17], accelerometers [12,15], acoustic emission [13,14], etcetera. Different studies have been also conducted in signal processing and feature extraction [18][19][20][21].…”
Section: Monitoring Modulementioning
confidence: 99%